A surface radio array for the enhancement of IceTop and its science prospects - Balagopal V., Aswathi; Haungs, Andreas; Huege, Tim; Schröder, Frank; Kleifges, Matthias; Schieler, Harald; Huber, Thomas; Renschler, Max (2018)
Radio detection of air showers in the current era has progressed immensely to effectively extract the information of air showers and their properties. It is mainly applied to the detection of cosmic rays and neutrinos. Primary cosmic rays with energies of hundreds of PeV have been successfully measured with the method of radio detection. Current radio experiments measuring such air showers mostly operate in the frequency range of 30-80 MHz. An optimization of the frequency band of operation can be done for maximizing the signal-tonoise ratio that can be achieved by an array of radio antennas at the South Pole, operated along with IceTop. Such an array can improve the reconstruction of air showers performed with IceTop. The prospects of using such an optimized radio array for measuring gamma-rays of PeV energies from the Galactic Center will be presented in this talk. The current tests of a prototype antenna for this purpose will also be ...